(untitled) (Revista Geoaraguaia, 2020)
Because of its special geochemical properties, lithium can be concentrated in sedimentary rocks. The current study was conducted on sedimentary units of the Jam 1:100000 sheet (NE Iran) by Concentration-Number(C-N) fractal models and staged factor analysis. Samples were based on stream sediment and lithogeochemical data. Concentration-Number fractal model was utilized to identify anomalous areas for lithium and the results were presented in the form of maps. According to the lithology of the area, which contains sedimentary units with various clay minerals, and the high correlation between lithium and three other elements (B, Rb, and Cs) in the anomalous area, an area in the southeast of Jam was found to contain the highest amount of lithium anomaly. This area should be further investigated in future studies. It is suggested that interested researchers use the two methods implemented in this study to explore lithium in sedimentary rocks and identify promising areas bearing lithium in Iran.